Association of Olfactory Impairment and Postoperative Cognitive Dysfunction in Elderly Patients - Lan, Yang; You, Zhi-jian; Du, Ruiming; Chen, Le-si; Wu, Jia-xuan (Frontiers in Molecular Biosciences, 2021)
This study investigates the impact of anesthesia on the change of olfactory function and cognitive function in elderly patients who undergo abdominal surgery. A total of 30 elderly patients who underwent abdominal surgery were recruited as the research subjects. The Connecticut Chemosensory Clinical Research Center (CCCRC) olfactory test was used to test the olfactory function and the Mini-mental State Examination （MMSE), Hopkins Verbal Learning Test - Revised (HVLT-R), Trail Making Test (TMT), Stroop Color Word Test (SCWT), Digit-Symbol Coding Test (DSCT) and Verbal Fluency Test (VFT) were used to assess their cognitive function before general anesthesia, and on the 3rd and 7th day post-anesthesia. The serum level of IL-1β, IL-6 and TNF-ɑ were measured before anesthesia and at 0,12,24h post-anesthesia. In total, 30 healthy volunteers who did not undergo anesthesia were used as the control group. The test results of all subjects were recorded and their correlations were analyzed. It was found that On the 3rd and 7th day post-anesthesia, the olfactory recognition threshold of patients in the surgical group was lower than that of control group with significant difference (P<0.05). On the 3rd and 7th postoperative day, the patient's short-term memory and delayed memory, attention and processing speed were decreased (P<0.05). On the 7th day post-anesthesia, delayed memory and processing ability were still decreased (P<0.05). In the surgical group，Spearman correlation analysis showed that the difference of olfactory recognition score on the 3rd and 7th day post-anesthesia was positively correlated with short-term memory and delayed memory of cognitive function .Compared with pre-anesthesia, the serum levels of IL-1β, IL-6 and TNF-ɑ in the surgical group were significantly increased at each time point after anesthesia. Collectively, abdominal surgery with general anesthesia in elderly patients may increase the level of serum inflammatory factors, induce olfactory impairment, particularly the decline of olfactory identification threshold and cause cognitive dysfunction with declined short-term memory, delayed memory and attention. There was a positive correlation between olfactory impairment and cognitive dysfunction after general anesthesia. Therefore, olfactory impairment could be an early indicator to guide early intervention for postoperative cognitive dysfunction.